Social Psycology - MYERS, David G. (Toronto : McGraw -Hill, 2004)
The rapid changes which have occurred in the content of social psychology, both in its concepts and in its data, have seemed to me to justify the appearance of a new textbook in the field. More particularly, the increasing concern of psychologists with other cultures has suggested that there might be some interest in an attempt at integration between psychology and ethnology.
Includes bibliography and index
Keywords: Social psychology. Psychology, Social